Time-dependent behaviour of circular steel tube confined reinforced concrete (STCRC) stub columns subjected to low axial load. (15th September 2021) - Guo, Yun-Long; Geng, Yue; Qu, Lian-Yu
Highlights: 490 day-long-term loading tests on 17 pairs of circular STCRC stub columns. Confinement effects and vertical load resistance contribution of the steel tube. Difference between the long-term deformation of STCRC columns and CFST columns. Abstract: Steel tube confined reinforced concrete (STCRC) columns have a promising future in high-rise buildings owing to their ease in connection, high bearing capacity, and excellent seismic behaviour. To date, no investigation is available for the time-dependent behaviour of STCRC columns despite of the numerous researches conducted on the short-term and seismic behaviour. This paper intends to experimentally study the time-dependent behaviour of STCRC columns. Seventeen pairs of circular STCRC stub columns were under sustained loading for 490 days. The experimental parameters include the concrete loading age, the concrete compressive strength, the steel ratio (i.e. the ratio of the steel tube area over the core concrete area), the longitudinal reinforcement ratio (i.e. the ratio of the longitudinal reinforcement area over the concrete area) and the bond condition of the steel–concrete interface. Special attention was given to study how, if any, the confinement effects and the vertical load resistance offered by the steel tube influence the time-dependent behaviour of the composite column. Key factors influencing the time effects of the STCRC columns were determined, and the difference between the long-term deformation of STCRC columns and that of traditional concrete-filled steel tubular (CFST) columns with the same steel consumption were compared. A numerical model was then proposed for calculating the long-term deformation of STCRC stub columns based on the cross-sectional analysis method and the step-by-step method, and was benchmarked against the available test results. Experimental results indicated that the static responses of STCRC were significantly influenced by time effects, which is much more pronounced than that of companion CFST columns. Within the parameter range considered in this investigation, both the confinement effects and the bond properties of the steel–concrete interface rarely influence the long-term behaviour of STCRC stub columns. The proposed numerical analysis method in this paper achieved reasonable accuracy for calculating the long-term deformation of STCRC stub columns, with the slope of regression line and the correlation coefficient of 1.013 and 0.916, respectively. It is worth highlighting that all the conclusions in this paper are only applicable within the parameter range in this paper, and further study is still required for more comprehensive insight in the long-term behaviour of STCRC columns.